Positive or Negative Effects of Technology Enhancement for Brand Placements? Memory of Brand Placements in 2D, 3D, and 4D Movies. Issue 4 (1st October 2016) - Terlutter, Ralf; Diehl, Sandra; Koinig, Isabell; Waiguny, Martin K. J.
Abstract : Brand placements in movies are common throughout the world. Within the last few years, 3D movie technology has experienced substantial growth in both cinemas and home entertainment. Furthermore, advanced cinemas also offer 4D experiences by adding scent, airflow or tactile stimuli to the 3D film. Based on the limited capacity model of information processing and the levels of processing effect theory, we conduct two studies to investigate how delivery modes of a 2D movie clip, compared to a 3D and a 4D (3D + scent) movie clip, influence recall and recognition of brands that are placed in either prominent or subtle ways. With regard to subtle placements, results from both studies demonstrate that the memory of subtle brand placements is negatively affected by the enhancement offered by 3D or 4D, as compared to 2D movies. With regard to prominent placements, results indicate that the memory of a highly prominent brand placement benefits from 3D, but not from 4D technology. This article addresses implications for research as well as for marketers and movie makers, while also outlining directions for further research.